The continuity between waking-life musical activities and music dreams - Vogelsang, Lukas; Schredl, Michael (Dreaming, 2016)
[Correction Notice: An Erratum for this article was reported in Vol 26(2) of Dreaming]. In the article, four errors appear in text due to production errors. In the introduction, second paragraph, the third sentence should read: Paul McCartney reported that he woke up with a lovely tune in his head and first he didn’t believe it was his own creation. In the Discussion section, second paragraph, the last phrase of the first sentence should read: but much higher compared with the sample of Schredl et al. (2015). In the Discussion section, the last phrase of the third paragraph should read: were much higher and, thus, detecting a substantial relationship was more likely. In the Discussion section, seventh paragraph, the second to the last sentence should read: This relationship has been shown for athletes.] As expressed in anecdotal reports, dreams have provided inspiration to both classical and popular musicians. According to the continuity hypothesis, engaging in music activities in the daytime should be related to the occurrence of music dreams. One-hundred and 44 participants (mostly psychology students, music students, and choir members) were asked to complete questionnaires about music-related waking-life activities and music in dreams. As expected, the amount of time invested in music activities during the day is directly related to the percentage of music dreams, thereby confirming the continuity hypothesis. Also, composing music in waking-life is related to a higher frequency of dreams with new music. Due to possible recall biases regarding retrospective measures for eliciting the percentage of music dreams, future research should follow up this study by using dream diaries in larger samples.
Gesehen am 01.07.2019